Long-Acting Reversible Contraception - Machado, Rogerio Bonassi; Monteiro, Ilza Maria Urbano; Magalhães, Jarbas; Guazzelli, Cristina Aparecida Falbo; Brito, Milena Bastos; Finotti, Marta Franco; Lubianca, Jaqueline Neves; Sakamoto, Luis Carlos; Franceschini, Silvio Antonio (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Unwanted pregnancy is a major public health problem both in developed and developing countries. Although the reduction in the rates of these pregnancies requires multifactorial approaches, increasing access to long-acting contraceptive methods can contribute significantly to change this scenario. In Brazil, gynecologists and obstetricians play a key role in contraceptive counseling, being decisive in the choice of long-acting reversible methods, characterized by intrauterine devices (IUDs) and the contraceptive implant. The vast scope due to the reduced number of situations to indicate long-acting methods should be emphasized in routine contraceptive counseling. On the other hand, gynecologists and obstetricians should adapt the techniques of insertion of long-acting methods, and engage in facilitating conditions to access these contraceptives through public and private health systems in Brazil. This study is part of a project called Diretrizes e Recomendações FEBRASGO (Guidelines and Recommendations of the FEBRASGO – Brazilian Federation of Gynecology and Obstetrics Associations from the Portuguese acronym). It aims to review the main characteristics of long-acting contraceptives and critically consider the current situation and future prospects to improve access to these methods, proposing practical recommendations of interest in the routine of gynecologists and obstetricians.
Keywords: contraception; contraceptive agents; contraceptive devices; intrauterine devices; progestins